Bittersweet Harvest, The Bracero Program 1942-1964, Illustrated Checklist - National Museum of American History, Kenneth E. Behring Center, Smithsonian Institution
An illustrated checklist of the Bittersweet Harvest: The Bracero Program 1942-1964 Exhibition, displaying dimensions and summaries of each piece. The summaries were used in the creation of a script used for self guided audio tours.